Digital Pranks and Islamic Ethics: A Critical Discourse Study of Aa Gym and Hadith on Humor - Nurul Hafizoh; Mukhammad Zamzami; Muhammad Lutfi; Wael Hegazy (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The phenomenon of pranks on social media has developed into a form of entertainment that is fraught with ethical and moral issues, especially when carried out without considering the psychological impact on the victims. Although it often receives positive responses from netizens, this type of content essentially indicates a tolerance for symbolic violence in the digital space. This article analyzes Abdullah Gymnastiar’s (Aa Gym) critical response to prank practices from an Islamic ethical perspective, which was uploaded to Aa Gym’s YouTube account on May 9, 2022, entitled “Celakanya Prank yang Mendzolimi Orang Lain-kajian singkat Aa Gym”, with reference to the hadith of the Prophet Muhammad about joking, particularly in Sunan Abī Dāwūd. This study uses Norman Fairclough’s Critical Discourse Analysis approach through three stages: (1) text analysis as a representation of something that contains a certain ideology because it wants to see how reality is formed in the text to identify lexical, sentence structure, rhetorical style, and intonation; (2) discourse practice analysis to understand the context of the production and dissemination of the message in digital media, and (3) socio-cultural practice analysis to relate the findings to Islamic ethical norms and the dynamics of online humor culture. This study explores the construction of language, moral values, and religious norms in Aa Gym’s digital dakwah content and its implications for public understanding of ethical boundaries in online humor culture. The analysis reveals that Aa Gym emphasizes the importance of responsible humor that entertains without hurting or degrading others. This study underscores the importance of ethical reflection on digital humor practices and the need to reevaluate the boundaries of decency in jokes. Thus, this article contributes to the discourse on media ethics and contemporary da‘wah, while highlighting the relevance of Islamic norms in responding to the challenges of popular culture in the digital age.